Selective area growth of AlN/GaN nanocolumns on (0001) and (11–22) GaN/sapphire for semi-polar and non-polar AlN pseudo-templates. (16th August 2017) - Bengoechea-Encabo, A; Albert, S; Müller, M; Xie, M–Y; Veit, P; Bertram, F; Sanchez-Garcia, M A; Zúñiga-Pérez, J; de Mierry, P; Christen, J; Calleja, E
Abstract: Despite the strong interest in optoelectronic devices working in the deep ultraviolet range, no suitable low cost, large-area, high-quality AlN substrates have been available up to now. The aim of this work is the selective area growth of AlN nanocolumns by plasma assisted molecular beam epitaxy on polar (0001) and semi-polar (11–22) GaN/sapphire templates. The resulting AlN nanocolumns are vertically oriented with semi-polar 1–103 top facets when grown on (0001) GaN/sapphire, or oriented at 58° from the template normal and exposing 1–100 non-polar top facets when growing on (11–22) GaN/sapphire, in both cases reaching filling factors ≥80%. In these kinds of arrays each nanostructure could function as a building block for an individual nano-device or, due to the large filling factor values, the overall array top surfaces could be seen as a quasi (semi-polar or non-polar) AlN pseudo-template.